2011
DOI: 10.1002/jsfa.4281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1-methylcyclopropene on tomato flavour components, shelf life and decay as influenced by harvest maturity and storage temperature

Abstract: Harvesting tomatoes with colour (BR), thereby eliminating IG fruits, and treating with 1-MCP resulted in better quality with adequate shelf life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 24 publications
3
23
0
Order By: Relevance
“…Many tomatoes grown for fresh consumption are picked when still firm and green, stored at low temperature, and exposed to exogenous ethylene to induce color and ripeness before reaching the supermarket shelf. Although effective in limiting postharvest losses, these procedures negatively affect tomato flavor, aroma, and texture [1]. The common use of mutants affected in ripening has similar negative impacts on flavor.…”
Section: Resultsmentioning
confidence: 99%
“…Many tomatoes grown for fresh consumption are picked when still firm and green, stored at low temperature, and exposed to exogenous ethylene to induce color and ripeness before reaching the supermarket shelf. Although effective in limiting postharvest losses, these procedures negatively affect tomato flavor, aroma, and texture [1]. The common use of mutants affected in ripening has similar negative impacts on flavor.…”
Section: Resultsmentioning
confidence: 99%
“…Juice sample color was analyzed for L *, a *, and b * values using a Minolta CR‐400 Chromameter (Konica Minolta, Sakai, Osaka, Japan) 19…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure , tomato fruit is consisted of pericarp and inner tissue (Van de Poel et al, ). A great number of studies have reported the volatile compositions in the whole fruit or pericarp tissue (Bai et al, ; Baldwin et al, ; Maul et al, ; Wang, Baldwin, Plotto, et al, ; Wang, Baldwin, Yu, & Bai, ; Wang, Baldwin, Zhao, et al, ); however, our understanding on volatile profile in inner tissue and its contribution to tomato aroma is still rudimentary.…”
Section: Introductionmentioning
confidence: 99%
“…This study will provide the researchers and consumers some useful information on volatile composition in inner tissue and its contribution to tomato aroma as well as the impact of different sampling methods on the volatile profile. For the analysis of tomato volatile profile, there are two methods usually applied: one only samples the pericarp (Bai et al, ), while the other samples pericarp and inner tissue together (Baldwin et al, ).…”
Section: Introductionmentioning
confidence: 99%